2021
DOI: 10.1161/strokeaha.120.031977
|View full text |Cite
|
Sign up to set email alerts
|

Early Thrombectomy Protects the Internal Capsule in Patients With Proximal Middle Cerebral Artery Occlusion

Abstract: Background and Purpose: Proximal middle cerebral artery (MCA) occlusions impede blood flow to the noncollateralized lenticulostriate artery territory. Previous work has shown that this almost inevitably leads to infarction of the dependent gray matter territories in the striate even if perfusion is restored by mechanical thrombectomy. Purpose of this analysis was to evaluate potential sparing of neighboring fiber tracts, ie, the internal capsule. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Furthermore, early initiation of EVT was linked to a higher chance of CST salvage. Of 25 patients with an onset-to-puncture time of ≤180 min, 19 (76.0%) achieved CST salvage after EVT, which is in line with the results regarding anterior circulation large-vessel occlusion stroke ( 10 ). However, these data should be interpreted with caution, as large heterogeneity exists in the infarct growth rate among patients with BAO and slow progressors may benefit from EVT beyond this time window ( 29 ).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Furthermore, early initiation of EVT was linked to a higher chance of CST salvage. Of 25 patients with an onset-to-puncture time of ≤180 min, 19 (76.0%) achieved CST salvage after EVT, which is in line with the results regarding anterior circulation large-vessel occlusion stroke ( 10 ). However, these data should be interpreted with caution, as large heterogeneity exists in the infarct growth rate among patients with BAO and slow progressors may benefit from EVT beyond this time window ( 29 ).…”
Section: Discussionsupporting
confidence: 83%
“…The strong association between the CST salvage and good clinical outcomes in our study indicated that the eloquence of certain brain areas could have profound effects on outcome after EVT ( 10 , 26 ) and it could be explained by the fact that the intact CST was a predictor of independent walking after stroke ( 27 ). We found that the extent of BAO was associated with CST salvage.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This finding is in line with previous studies that have evidenced that CST affection in chronic stroke stages correlates with more severe persistent deficits after spontaneous recovery 15,16 and worse outcome after MT. [27][28][29][30] However, there are only a few studies that have looked at the structural state of distinct key regions of the human motor network within the first hours after symptom onset and evaluated its association with functional outcome. Preinterventional magnetic resonance imaging-derived complete infarction of basal ganglia, 31 primary motor area, and bilateral centrum semiovale 32 was associated with worse NIHSS at discharge and poor mRS at follow-up, respectively.…”
Section: Discussionmentioning
confidence: 99%